Zoledronic acid effectiveness against breast cancer metastases - a role for estrogen in the microenvironment? - Steinman, Richard A (BioMed Central, 2012)
Zoledronic acid (ZA) is an imidazole-containing bisphosphonate that has been extensively studied as an osteoclast inhibitor. ZA decreases bone turnover and has been effective in limiting osteolysis in metastatic cancers, including breast cancer. Recent clinical trials that demonstrated enhancement of disease-free survival by bisphosphonates have prompted interest in bisphosphonates as anti-cancer agents. ZA, for example, increased disease-free survival in postmenopausal and in premenopausal, hormone-suppressed breast cancer patients. Intriguingly, however, there was a lack of an anti-cancer effect of ZA in premenopausal women without ovarian suppression. These observations have prompted the conjecture that anti-cancer effects of ZA are limited to estrogen-poor environments. This review explores possible mechanisms compatible with differences in ZA activity in premenopausal women compared with postmenopausal (or hormone-suppressed) women.